A afetividade nas práticas pedagógicas: atitudes e expressões verbais nas interações professora- crianças, sob a perspectiva de Henri Wallon - Galiani, Simone da Silva [UNESP] (2013)
This research project presents starts with an investigation realized into the presence and also the characteristics of affectivity in the pedagogical practice of a child education’s teacher. The research`s process began linked with the research way of the Post-Graduate Education at UNESP – university located in Presidente Prudente, SP, called Childhood and Education and it adopted as the object of study the affectivity in early childhood education in the walloniana’s perspective of theory, in order to reflect about into the established pedagogical relations in the construction process of the interactions by children that are between 4 and 5 years old. Several studies, revealed that the affectivity (emotions, feelings and passions) is present in the educational context so it requires the actual presence of adults in child development. The research was based on a qualitative approach, using the case’s study, where the participants were a teacher and also twenty-two child students in an institution of a municipal school in Presidente Prudente-SP. It was used as techniques for gathering data, the classroom observations and a semi-structured interview with the teacher having in mind to know her concepts about affectivity and also her presence in the classroom. The observations that were done between the months of April and June of 2012 through interaction activities that the pedagogical practice used by the teacher summed up in two aspects that are present in the affective dimension: attitudes and verbal expressions. About the first one, it became clear that although the affection is constantly present in all moments of interaction in the educational environment, it still needs to be worked so to build meaningful interactions by children that is sometimes presented as something positive (dialogue, respect, care), and other times it was revealed as the shallowness in teacher-child relationships...